Невмотивований відвід кандидату у присяжні у кримінальному процесі (порівняльно-правове дослідження) - Крикунов, О; Денісова, Г; Krykunov, A; Denisova, G (СНУ ім.Лесі Українки, 2019)
У статті з’ясовано історичний та етимологічний аспект, процесуальну природу невмотивованого відводу кандидату у присяжні, його значення для формування складу суду присяжних у кримінальному провадженні відповідно до інтересу його сторін. Узагальнено доступні пам’ятки права, акти законодавства та судову практику низки держав світу. З’ясовано ситуації, за яких доцільним є заявлення невмотивованого відводу кандидату у присяжні. Розглянуто юридичні та психологічні рекомендації закордонних фахівців. Автори дійшли висновку, що запровадження права на невмотивований відвід кандидату у присяжні у наше чинне законодавство як окремий крок для його вдосконалення не видається доцільним. The article clarifies the historical and etymological aspects and the procedural nature of the peremptory challenge of the jury candidate, its significance for the formation of an impartial the court in criminal proceedings. In the context of the subject of the study, the authors generalize historical legal documents, available legislature and judicial practice of a number of states, belonging to the Anglo-American and Romano-Germanic legal systems. The study focuses on the situations in which it is expedient to declare an peremptory challenge to a jury candidate. The legal and psychological recommendations of foreign experts, who apply in their own practice the right to peremptory challenge of a candidate in jury, are considered. Іn the world there is a tendency to refuse or limit peremptory challenge to jury candidates. The introduction of the right to peremptory challenge of a candidate in a jury into our current legislation as a separate step for its improvement does not seem appropriate. The ECtHR's approach, which is incompatible with the idea of peremptory challenge, is of fundamental importance to the legal system of Ukraine. The experience of other states, that have waived or restricted the right to peremptory challenge, should not be ignored.
Peremptory Challenge of the Candidate to Jury in Criminal Proceedings (Comparative Legal Study)
Keywords: суд присяжних; відвід; невмотивований відвід; кримінальний процес; jury candidate; jury trial; discharge; unmotivated discharge; criminal process